The end-of-life needs of Aboriginal and immigrant communities: a challenge to conventional medical models - Leonard, Rosemary; Paton, Joy; Hinton, Peta; Greenaway, Sally; Thomson, Jody (Frontiers in Public Health, 2023)
This article presents insights from research investigating the end-of-life (EOL) needs of Aboriginal and culturally and linguistically diverse (CaLD) people living in Western Sydney, Australia, which has a large rapidly growing region with a highly diverse population and on average low socioeconomic status. The research partners, Western Sydney Local Health District, provided an Advisory Panel was made up of representatives of Supportive and Palliative Medicine, Bereavement support, Aboriginal Health, and Multicultural Health. The research aimed to generate findings to support the delivery of culturally sensitive services in the public health system. The multimethod design and the conduct of the research was informed by the literature on researching with marginalized groups which highlights the ethical considerations needed to avoid replicating past injustices. Qualitative data from key informants and focus groups revealed seven themes and also some suggested solutions which were relevant across several themes. The seven themes were: the Need for trusted relationships; Unwillingness to talk about death; Lack of understanding of key services; Decision-making and obtaining consent from the patient; Appropriate physical spaces; Cultural practices around EOL; and Language barriers. Within each theme a variety of cultural beliefs and practices were revealed that conflicted with mainstream medical systems and would need for changes in mainstream medical systems. Compassionate communities was identified as model to support the necessary changes.